ECONOMIC MENTALITY AS A FACTOR OF DEVELOPMENT OF INSTITUTIONAL ENVIRONMENT - V. Osetsky (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article defines the concept of economic mentality as informal institution, analyzes the basic approaches to the interpretation of this category in institutional theory, the structure of the institutional environment, indicates the place and role of economic mentality in the system of institutional factors of economic development, outlines the prospects for further research of this problem.